2015
DOI: 10.1016/j.pedneo.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neuron-specific Enolase Levels in Preterm and Term Newborns and in Infants 1–3 Months of Age

Abstract: Our findings suggest that adult reference values should not be applied to the preterm and term age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However and notably, pediatric populations were not nearly as frequently studied as adult TBI patients. The reference levels for healthy pediatric populations (especially the first year) of S100B and NSE have both been shown to be significantly higher than for adults (factor ×2–4) (124, 125). Nevertheless, during traumatic conditions, similar trajectories to adults are seen in pediatric populations, and serum dynamics are likely a marker of injury severity and progression not requiring separate reference levels per age group.…”
Section: Discussionmentioning
confidence: 99%
“…However and notably, pediatric populations were not nearly as frequently studied as adult TBI patients. The reference levels for healthy pediatric populations (especially the first year) of S100B and NSE have both been shown to be significantly higher than for adults (factor ×2–4) (124, 125). Nevertheless, during traumatic conditions, similar trajectories to adults are seen in pediatric populations, and serum dynamics are likely a marker of injury severity and progression not requiring separate reference levels per age group.…”
Section: Discussionmentioning
confidence: 99%
“…All six concentrations differed substantially from the other controls (mean > ×10 higher), interpreted as a consequence of the capillary sampling and hence these six observations were excluded. Abbasoglu et al [17] have reported high NSE levels in healthy preterm and term newborns.…”
Section: Concentrations Of Cga Cgb and Nsementioning
confidence: 97%
“…LDH is an enzyme that plays an important role in glycolysis and can be used as an indicator of the systemic tumor burden. NSE is also an enzyme takes part in the glycolysis process; it exists in neurons and nerve-derived cells and is a highly specific and sensitive indicator of NB [18] . An LDH concentration of > 1000 U/L and NSE concentration of > 100 ng/ml are poor prognostic factors [19] .…”
Section: Discussionmentioning
confidence: 99%